2018
DOI: 10.1111/jnc.14262
|View full text |Cite
|
Sign up to set email alerts
|

Repair gene O6‐methylguanine‐DNA methyltransferase is controlled by SP1 and up‐regulated by glucocorticoids, but not by temozolomide and radiation

Abstract: Therapy of malignant glioma relies on treatment with the O -methylating agent temozolomide (TMZ) concomitant with ionizing radiation followed by adjuvant TMZ. For the treatment of recurrences, DNA chloroethylating drugs are also used. The main killing lesion induced by these drugs is O -alkylguanine. Since this damage is repaired by O -methylguanine-DNA methyltransferase (MGMT), the repair enzyme represents a most important factor of drug resistance, limiting the therapy of malignant high-grade gliomas. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…It has recently been documented that MGMT expression is associated with SP1 expression in glioma cell lines. Since knockdown of SP1 strongly reduced MGMT protein expression, SP1 is one of the main factors regulating MGMT [34]. MGMT expression also depends on p53, a transcription factor that sequesters SP1 and prevents its binding to MGMT [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been documented that MGMT expression is associated with SP1 expression in glioma cell lines. Since knockdown of SP1 strongly reduced MGMT protein expression, SP1 is one of the main factors regulating MGMT [34]. MGMT expression also depends on p53, a transcription factor that sequesters SP1 and prevents its binding to MGMT [34].…”
Section: Discussionmentioning
confidence: 99%
“…Since knockdown of SP1 strongly reduced MGMT protein expression, SP1 is one of the main factors regulating MGMT [34]. MGMT expression also depends on p53, a transcription factor that sequesters SP1 and prevents its binding to MGMT [34]. Additionally, there is evidence of mifepristone increasing apoptosis due to p53 activation in several cancer cell lines [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, increased G2/M arrest and decreased subG1 fraction with dexamethasone pretreatment may be a result of increased DNA double-strand break repair. Aasland et al 1) had demonstrated that O 6 -methylguanine-DNA methyltransferase (MGMT), which is a significant biomarker for glioblastoma concomitant chemoradiotherapy with temozolomide, was induced by glucocorticoids because the MGMT promotor site has two glucocorticoid response elements (GRE) in HeLa S3 cells. Later, they evaluated that MGMT expression is not affected by radiation or temozolomide and is primarily controlled by specificity protein 1 (SP1) transcription factor in various malignant glioma cell lines.…”
Section: Possible Mechanism Of Action Of Dexamethasone In Irradiated mentioning
confidence: 99%
“…For example, in the treatment of glioblastoma, dexamethasone can reduce the efficacy of radiotherapy. Aasland D found that radiotherapy could not activate the MGMT promoter of glioblastoma, while dexamethasone induced MGMT gene in cases of unmethylation of MGMT promoter, and may lead to further increase in temozolomide resistance, and reduce the effect of radiotherapy [11]. Luedi MM reported that dexamethasone reduced temozolomide-induced apoptosis in glioma stem cells and reduced radiation sensitivity.…”
Section: Discussionmentioning
confidence: 99%